Asuhan Keperawatan Keluarga Tn. K Dengan Gangguan Sistem Persyarafan: Stroke Pada Tn. K Di Desa Kauman RT 01 RW 04 Kecamatan Tonjong Kabupaten Brebes - Bunga Ramadhani; Esti Nur Janah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Stroke is a neurological condition caused by disruption of blood flow to the brain due to blockage or rupture of blood vessels, leading to nerve cell death. WHO (2022) recorded more than 12 million new stroke cases annually, with a prevalence in Brebes Regency reaching 27.83 per mil. The high incidence of stroke accompanied by physical mobility impairment and the family's lack of knowledge about its management highlights the importance of comprehensive family nursing care. This study aims to apply a complete nursing care process including assessment, diagnosis, intervention, implementation, and evaluation to the family of Mr. K with a stroke case. The method used is descriptive with a case study approach through family nursing care. Assessment findings revealed that the patient had experienced stroke for approximately 7 years with a history of hypertension, weakness of the right extremities, decreased muscle strength, blood pressure of 160/90 mmHg, and the family did not understand how to care for stroke at home. Two nursing diagnoses were established: ineffective health maintenance in the family and impaired physical mobility. Interventions included health education about stroke, Range of Motion (ROM) exercises, and rubber ball grip therapy involving the family as caregivers. After 2 days of implementation, both nursing diagnoses were resolved: ineffective health maintenance in the family was resolved and impaired physical mobility was resolved.